Efeito terapêutico do exercício aeróbico em um modelo da doença de parkinson induzida por 6-hidroxidopamina em camundongos dissertação de mestrado - Goes, André Tiago Rossito (2013)
Parkinson’s disease (PD) is characterized by progressive degeneration of dopaminergic neurons in the nigrostriatal system and dopamine (DA) depletion in the striatum. Exercise has been showed to be a promising non-pharmacological approach to reduce the risk of neurodegeneration disease. This study was designed to investigate the potential neuroprotective effect of swimming training (ST) in a mouse model of PD induced by 6-hydroxydopamine (6-OHDA) in mice. The present study demonstrated that an 4-week ST was effective in attenuating the following impairments resulting from 6-OHDA exposure: depressive-like behavior in tail suspension test; increase in number of falls in rota rod test; impairment on long-term memory in the object recognition test; increased reactive species levels; inhibition of the glutathione peroxidase (GPx) activity and rise the glutathione reductase (GR) and glutathione S-transferase (GST) activities; increased interleukin 1-beta (IL-1β) level and decrease the levels of DA, homovanillic acid (HVA) and 3,4-dihydroxyphenylacetic acid (DOPAC)). The mechanisms involved in this study are the modulation of GPx, GR and GST activities and IL-1β level in a PD model induced by 6-OHDA in mice, and hence protecting against the decrease of DA, DOPAC and HVA levels in striatum of mice. These findings reinforce that one of the effects induced by exercise on neurodegenerative disease, such as PD, is due to antioxidant and anti-inflammatory properties. We suggest that exercise attenuates cognitive and motor declines, depression, oxidative stress, and neuroinflammation induced by 6-OHDA supporting the hypothesis that exercise can be used as a non-pharmacological tool to reduce the signs of PD.